(untitled) (Iranian Journal of Kidney Diseases, 2020)
Introduction. Pulmonary hypertension (PHTN) is a common complication in patients with chronic kidney disease. Delayed Graft Function (DGF), on the other hand; is an essential complication after kidney transplantation. These two complications increase morbidity and mortality in patients. The effect of PHTN on cardiovascular and graft blood supply, as well as the same mechanisms underlying PTHN and DGF; led us to investigate the relationship between them. Methods. In this retrospective cohort study, 306 patients aged 18 years or older who underwent kidney transplantation at our center over a 4-year were enrolled. PTHN was diagnosed by transthoracic echocardiography performed by a cardiologist. DGF refers to the cases where the patient needs dialysis in the first week after kidney transplantation or if serum creatinine is ≥ 3 mg/dL on the 5th day after surgery. Results. The prevalence of PHTN was 43 (14.1%), and the prevalence of DGF was 80 (26.1%). PHTN was not correlated with age, sex, duration of dialysis, type of dialysis, and cause of renal failure. But DGF was associated with the duration and type of dialysis. DGF was found to be higher in patients undergoing hemodialysis (P < .05), and patients with a higher mean duration of dialysis were also more likely to have DGF (P < .05). Also, we concluded that there was a significant relationship between PHTN and DGF (P < .05), meaning that patients with PTHN before transplantation were more likely to develop DFG. Conclusion. This study found that pre-transplant PTHN is an independent predictor of DGF in renal transplant patients.